Sifat Fisikokimia dan Profil Asam Lemak Minyak Ikan dari Kepala Kakap Merah (Lutjanus malabaricus) - Desiana Nuriza Putri; Yessi Maulidhia Nugrahani Wibowo; Erika Novena Santoso; Putri Romadhani (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
Red snapper processing industry (Lutjanus malabaricus) produces more than 50% solid waste and by-products, so the by-product of red snapper processing, viz., the fish head is a potential source of omega-3. This study aimed to determine the rendering method and extraction time, producing the best quality fish oil that is rich in omega-3 from the red snapper head. The samples were taken from a fish fillet industry in Pasuruan, East Java, Indonesia. Randomized Block Design (RBD) with two factors has been used to evaluate different rendering methods (wet and dry rendering) and extraction time (1, 2, and 3 hours) in triplicate. The results showed that the best fish oil was produced by wet rendering method in 1 hour of extraction time, achieving peroxide number 0.98 meq/kg, free fatty acid 1.02%, acid number 2.02%, extraction yield 9.02%, water content 4.22% (wb), brightness (L) 43.5, redness level (a) -0.9, and yellowish level (b) 2.7. The fish oil consisted of 31 types of fatty acids with palmitic acid as the major fatty acid. Additionally, the oil also contained omega-3 (14.02%) as well as AA, DHA, and EPA.